Furcellaran Surface Deposition and Its Potential in Biomedical Applications - Štěpánková, Kateřina; Ozaltin, Kadir; Pelková, Jana; Pištěková, Hana; Karakurt, Ilkay; Káčerová, Simona; Lehocky, Marian; Humpolicek, Petr; Vesel, Alenka; Mozetic, Miran (International journal of molecular sciences, 2022)
Surface coatings of materials by polysaccharide polymers are an acknowledged strategy to modulate interfacial biocompatibility. Polysaccharides from various algal species represent an attractive source of structurally diverse compounds that have found application in the biomedical field. Furcellaran obtained from the red algae Furcellaria lumbricalis is a potential candidate for biomedical applications due to its gelation properties and mechanical strength. In the present study, immobilization of furcellaran onto polyethylene terephthalate surfaces by a multistep approach was studied. In this approach, N-allylmethylamine was grafted onto a functionalized polyethylene terephthalate (PET) surface via air plasma treatment. Furcellaran, as a bioactive agent, was anchored on such substrates. Surface characteristics were measured by means of contact angle measurements, X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). Subsequently, samples were subjected to selected cell interaction assays, such as antibacterial activity, anticoagulant activity, fibroblasts and stem cell cytocompatibility, to investigate the Furcellaran potential in biomedical applications. Based on these results, furcellaran-coated PET films showed significantly improved embryonic stem cell (ESC) proliferation compared to the initial untreated material.
Keywords: Polymers; antibakteriální látky; povrchové vlastnosti; Alginates; polymery; Anti-Bacterial Agents; algináty; rostlinné gumy; Polyethylene Terephthalates; Plant Gums; polyethylentereftaláty; Surface Properties